‘I’ādah al-Tarkīb li Afkāri al-‘Ulamā’ al-Sundāwīyīn - Moeflich Hasbullah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
This article is an initial endeavor to reconstruct the thoughts of Sundanese ulama. At the start, a number of dispersed writings about Sundanese ulama is introduced. Some of them concern popular works that are easily available in Indonesia such as Dadan Wildan's dissertation (2003)Cerita Sunan Gunung Djati: Keterjalinan Antara Fiksi dan Fakta. Suatu Kajian Pertalian Antarnaskah, Isi, dan Analisa Sejarah dalam Naskah-naskah Tradisi Cirebon (The story of Sunan Gunung Djati: the intertwinement of fiction and fact. A study of intertextuality, content, and a historical analysis of the Cirebon manuscript tradition). Aliefya M. Santri (1987) wrote a short paper on Martabat Alam Tujuh (Martabat Kang Pipitu), the work of Syekh Abdul Muhyi Pamijahan Tasikmalaya, the 16th century ulama who spread Islam in south West Java. Also there is Didin Hafiduddin who, in 1987 studied Syekh Nawawi al-Bantani, the great Sundsneseulama of the 19th century from Banten, and more specifically his Tafsir al-Munir.DOI: 10.15408/sdi.v15i3.527